Business Ethics and the Transitional Economy: A Tale of Two Modernities - Barclay, Jean (Journal of business ethics, 2003)
The concept of the Transitional Economy denotes the problematic processes of change confronting nations wishing to achieve levels of economic development comparable with that of Western nations. Such an objective is problematic, as these nations may also be said to be in a state of transition. Globalization and E-commerce have necessitated a reconsideration of the nature of business activity and its implications for both society and the individual., Writers such as Gray (1998) warn against the "refashioning" of other nations in the image of the American free market. Business ethics can be seen as a symbolic expression of Beck's (1992) concern with the implications of Risk Society and the uncertainties arising from the realization that scientific, technological, and economic progress are not necessarily concomitant with social, cultural, and political progress. Locating business ethics within the theoretical context of Reflexive Modernity provides a means of evaluating the contribution that it can make to providing a critical forum for considering the ways in which business organisations are responding to concerns regarding business activity. (168)